2021
DOI: 10.1016/j.neuropharm.2021.108841
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2-associated cytokine storm during pregnancy as a possible risk factor for neuropsychiatric disorder development in post-pandemic infants

Abstract: A strong association between perinatal viral infections and neurodevelopmental disorders has been established. Both the direct contact of the virus with the developing brain and the strong maternal immune response originated by viral infections can impair proper neurodevelopment. Coronavirus disease 2019 (COVID-19), caused by the highly-infectious severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is currently responsible for a large global outbreak and is a major public health issue. While initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 91 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…The potential for neurodevelopmental morbidity in offspring exposed prenatally to SARS-CoV-2 is therefore of great concern. Given the large number of exposed individuals, even a modest increase in risk for adverse offspring neurodevelopment would still have a massive public health impact [15][16][17][18][19][20]. More than 59 million people in the United States and 300 million worldwide have been diagnosed with coronavirus disease 2019 (COVID-19) i , including over 155 500 pregnant women in the United States [21].…”
Section: Potential Transgenerational Impact Of Viral Infections In Pr...mentioning
confidence: 99%
“…The potential for neurodevelopmental morbidity in offspring exposed prenatally to SARS-CoV-2 is therefore of great concern. Given the large number of exposed individuals, even a modest increase in risk for adverse offspring neurodevelopment would still have a massive public health impact [15][16][17][18][19][20]. More than 59 million people in the United States and 300 million worldwide have been diagnosed with coronavirus disease 2019 (COVID-19) i , including over 155 500 pregnant women in the United States [21].…”
Section: Potential Transgenerational Impact Of Viral Infections In Pr...mentioning
confidence: 99%
“…Ian was born just prior to the COVID‐19 pandemic but was not infected with the virus in utero or during his first years of life, which has been associated with neurodevelopmental delays in a small number of papers. 30 , 31 There are other reports of developmental delays in children born during the pandemic, 32 , 33 , 34 whether exposed to the virus or not, but no published reports of transient autism symptoms. Ian did not experience any significant changes in his exposure to other children or social situations in the short period over which the autism symptoms abated.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have observed placental invasion by immunohistochemical analysis and electron microscopy [ 125 , 126 ], and there are case reports which detected the virus in one infant and one fetus suffering from COVID-19 [ 127 , 128 ]. The concern for harmful effects on the developing brain due to SARS-CoV-2 remains, as it is well-documented that maternal infection is a risk factor for neurodevelopmental disorders including autism spectrum disorder and schizophrenia [ 129 , 130 , 131 , 132 ]. The main proposed key events are associated with the increased cytokine storm and hyperinflammation observed in pregnant women with COVID-19 and the loss of functional placenta integrity.…”
Section: Additional Factors Impacting Neurological Effects Of Covid-19mentioning
confidence: 99%